The discriminative power of the interval shuttle run test and the maximum multistage shuttle run test for playing level of soccer - Lemmink, K. A. P. M.; Verheijen, R.; Visscher, C. (The Journal of Sports Medicine and Physical Fitness, 2004)
AIM: The purpose of this study was to examine the discriminative power of the recently developed Interval Shuttle Run Test (ISRT) and the widely used Maximal Multistage 20 m Shuttle Run Test (MMSRT) for soccer players at different levels of competition. The main difference between the tests is that the exercise mode of the ISRT is not continuous but intermittent. Instead of 60 s of running per stage in the MMSRT, 30 s of running are alternated with 15 s of walking, twice per stage. METHODS: Comparative study: within a 2-week period, 81 male soccer players at the Dutch premier league professional, premier league and 3rd division amateur levels performed the ISRT and the MMSRT. The total number of runs was scored for both tests. RESULTS: Only the ISRT distinguished between levels of competition. In general, the ISRT correlated moderately with the MMSRT for players of different levels of competition (rP: 0.52-0.83). CONCLUSIONS: In contrast to the MMSRT, the ISRT shows discriminative power for soccer players at different levels of competition supporting the validity of the ISRT for measuring endurance in a more soccer-specific way. As a result of the intermittent character of the ISRT the energetics of the ISRT and the MMSRT are not closely related.